Planning, markets, and hospitals - Mohan, John, 1958- (Routledge, 2002)
"Improving access to hospital services has been a goal of public policy in Britain for over seventy years, but the means by which this goal is to be attained have changed significantly over time. Drawing substantially on original research, Planning, Markets and Hospitals represents a systematic attempt to assess the strengths and weaknesses of different forms of planning and coordination of hospital development."